Serotonin and consciousness – A reappraisal - Müller, Christian P. (Behavioural Brain Research, 2022)
The serotonergic system of the brain is a major modulator of behaviour. Here we describe a re-appraisal of its function for consciousness based on anatomical, functional and pharmacological data. For a better understanding, the current model of consciousness is expanded. Two parallel streams of conscious flow are distinguished. A flow of conscious content and an affective consciousness flow. While conscious content flow has its functional equivalent in the activity of higher cortico-cortical and cortico-thalamic networks, affective conscious flow originates in segregated deeper brain structures for single emotions. It is hypothesized that single emotional networks converge on serotonergic and other modulatory transmitter neurons in the brainstem where a bound percept of an affective conscious flow is formed. This is then dispersed to cortical and thalamic networks, where it is time locked with conscious content flow at the level of these networks. Serotonin acts in concert with other modulatory systems of the brain stem with some possible specialization on single emotions. Together, these systems signal a bound percept of affective conscious flow. Dysfunctions in the serotonergic system may not only give rise to behavioural and somatic symptoms, but also essentially affect the coupling of conscious affective flow with conscious content flow, leading to the affect-stained subjective side of mental disorders like anxiety, depression, or schizophrenia. The present model is an attempt to integrate the growing insights into serotonergic system function. However, it is acknowledged, that several key claims are still at a heuristic level that need further empirical support.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Affective consciousness; Conscious content; Consciousness; Flow; Serotonin